Diamonds Are Not Forever : Botswana Medium-term Fiscal Sustainability - Kojo, Naoko C. (2012)
This paper analyzes Botswana's medium-term fiscal sustainability in view of the expected depletion of diamonds in the future. The analysis shows that in the absence of policy adjustments, Botswana's current fiscal policy strategy is unsustainable over the longer term, which could endanger macroeconomic stability and Botswana's reputation as Africa's success story. Ensuring medium-term sustainability of Botswana's public finances requires stronger revenue collection, through improved revenue administration, greater tax enforcement, and the rationalization of tax exemptions in order to realize the full revenue potential. Opportunities also exist to generate more revenue from the non-mining sector through changes in the tax regime. At the same time, the government needs to maximize the effectiveness of public expenditure and bring down public spending to levels that are more in line with long-term revenue prospects. A greater control over the public sector wage bill is critically important. In-house capacity for macroeconomic monitoring and fiscal analysis also needs to be enhanced further. Looking ahead, growth of a dynamic non-mining sector is crucial for Botswana not only from the fiscal sustainability point of view, but from the point of view of achieving balanced development that will create jobs and deliver durable reduction in poverty and inequality. Fiscal policy will have to play a central role in this process.